Tuberculosis diagnosis through image processing - Kamal, Nahid; Islam, Subrina; Asad, Al Faysal Bin; Khatun, Sumaiya (BRAC University, 2017)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2017.